Evaluating resident involvement and the 'July effect' in parotidectomy. Issue 5 (29th May 2021) - Benito, D A; Mamidi, I; Pasick, L J; Sparks, A D; Badger, C; Thakkar, P; Goodman, J F; Joshi, A S
Abstract: Objective: This study aimed to evaluate the effect of resident involvement and the 'July effect' on peri-operative complications after parotidectomy. Method: The American College of Surgeons National Surgical Quality Improvement Program database was queried for parotidectomy procedures with resident involvement between 2005 and 2014. Results: There were 11 733 cases were identified, of which 932 involved resident participation (7.9 per cent). Resident involvement resulted in a significantly lower reoperation rate (adjusted odds ratio, 0.18; 95 per cent confidence interval, 0.05–0.73; p = 0.02) and readmission rate (adjusted odds ratios 0.30; 95 per cent confidence interval, 0.11–0.80; p = 0.02). However, resident involvement was associated with a mean 24 minutes longer adjusted operative time and 23.5 per cent longer adjusted total hospital length of stay (respective p < 0.01). No significant difference in surgical or medical complication rates or mortality was found when comparing cases among academic quarters. Conclusion: Resident participation is associated with significantly decreased reoperation and readmission rates as well as longer mean operative times and total length of stay. Resident transitions during July are not associated with increased risk of adverse peri-operative outcomes after parotidectomy.